An ecotoxicological risk model for the microplastics in arctic waters. (15th December 2022) - Saeed, Mohammad Sadiq; Halim, Syeda Zohra; Fahd, Faisal; Khan, Faisal; Sadiq, Rehan; Chen, Bing
Abstract: The risk posed to Arctic marine life by microplastics, a Contaminants of Emerging Arctic Concern (CEAC), is poorly known. The reason is the limited understanding of the dose-response relationship due to the region's peculiar environmental and geophysical properties and the unique physiological properties of the species living there. The properties of microplastics in the region and their distribution across the oceanic profile further complicate the problem. This paper addresses the knowledge gap by proposing a novel comprehensive ecotoxicity model. The model uses oxidative stress caused by the Reactive Oxygen Species (ROS) to assess cell mortality. Cell mortality has been used as an indicator of ecological risk. The model is implemented in the Bayesian Network (BN) framework to evaluate the cytotoxicity, measured as the probability of causing mortality. The work enhances the understanding and assessment of the cytotoxicity of microplastics in polar cod and associated risks. Graphical abstract: Image 1 Highlights: A novel approach for estimating risk of microplastic ingestion by Arctic aquatic biota is presented. This risk evaluation approach is applied to polar cod. A novel Bayesian Network model to predict cell death probabilities is described. The model is tested across a wide range of ecological conditions.